POTENSI PAJAK PENGHASILAN PEDAGANG PENGUMPUL TANDAN BUAH SEGAR (TBS) KELAPA SAWIT (STUDI DI KPP ABC) - M. Otryadi Naufal; Suparna Wijaya (STIE Mahardhika, 2022)
Palm oil collector traders are entities or individuals whose business activities are collecting oil palm plantation products in the form of oil palm fresh fruit bunches (FFB) and selling them to industrial business entities or exporters engaged in the plantation sector. The purpose of the study was to determine the potential income tax, the steps that have been taken and the obstacles, the realization of tax revenue for the collectors of Fresh Fruit Bunches (FFB) of oil palm at the Tax Service Office (KPP) ABC. The research method used is descriptive qualitative. The results of the study show that the potential taxes of palm oil collectors are PPh Article 21, PPh Article 22, PPh Article 23, PPh Article 25/29, Final PPh Article 4 paragraph (2) including the MSME taxation provisions. Steps that have been taken are socialization and appeals to taxpayers. The obstacles are geography, human resources, and awareness of taxpayers. Meanwhile, the realization of tax revenue is quite good and shows an increase, especially in Article 22 Income Tax.